2012
DOI: 10.1001/archpediatrics.2012.765
|View full text |Cite
|
Sign up to set email alerts
|

Use of Olive Oil for the Treatment of Seborrheic Dermatitis in Children

Abstract: Use of Olive Oil for the Treatment of Seborrheic Dermatitis in Children S eborrheic dermatitis is a common complaint brought to pediatricians. Also known as "cradle cap" in infants and "dandruff" in adolescents, the condition is believed to be triggered by Malassezia yeasts. 1 The natural course correlates androgen-driven excess sebum production: spontaneous improvement by age 1 year and reoccurrence with puberty. Treatment of this condition has supported a billion dollar market for overthe-counter treatments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…In addition, olive oil (as compared to other natural oils such as sunflower oil) has actually been shown to damage the skin barrier instead of repairing it ). Thus, patients should be advised not to apply plant oils such as olive oil to the areas (Siegried and Glenn 2012 ). It has been suggested that an inorganic oil such as mineral oil may be a better alternative if patients insist on the application of oil for this condition.…”
Section: Chapter 14mentioning
confidence: 99%
“…In addition, olive oil (as compared to other natural oils such as sunflower oil) has actually been shown to damage the skin barrier instead of repairing it ). Thus, patients should be advised not to apply plant oils such as olive oil to the areas (Siegried and Glenn 2012 ). It has been suggested that an inorganic oil such as mineral oil may be a better alternative if patients insist on the application of oil for this condition.…”
Section: Chapter 14mentioning
confidence: 99%
“…Still, its use for certain cutaneous diseases such as seborrheic dermatitis should be approached with caution because olive oil is used as a standard in vitro culture medium for Malassezia species . Olive oil contains saturated and unsaturated fatty acids, which may stimulate growth of Malassezia and induce inflammation, respectively …”
Section: Olive Oilmentioning
confidence: 99%
“…22 Olive oil contains saturated and unsaturated fatty acids, which may stimulate growth of Malassezia and induce inflammation, respectively. 23 It is also important to consider the risk of allergic contact dermatitis (ACD) in the context of AD. 24 On rare occasions, olive oil has been reported to cause irritant contact dermatitis and ACD.…”
Section: Olive Oilmentioning
confidence: 99%
“…It has also been shown that olive oil exerts detrimental effects on the neonatal skin. 39 Increased systemic absorption of evening primrose oil may rarely lower the blood pressure 40 and lead to prolonged bleeding time. 38 Some researchers have also cautioned that vegetable oils like olive oil may encourage Malassezia overgrowth, and the excessive unsaturated fatty acids produced by the digestion of fat by these yeasts may augment inflammation in seborrheic dermatitis and other dermatoses linked with Malassezia.…”
Section: Adverse Effects Of Vegetable Oilsmentioning
confidence: 99%